Coke combustion in fluidized bed: A multi-disciplinary lab experiment - Joel M. Silva (2017)
A multi-disciplinary pilot-scale setup was assembled with the purpose of studying coupled mass transport and chemical reaction phenomena during coke combustion in a fluidized bed. Such experimental work has been integrated in the program of a laboratory course (4th year) of the Integrated Master in Chemical Engineering at FEUP (Faculty of EngineeringUniversity of Porto). This way students deal with a systematic multi-variable study of a complex system involving an heterogeneous (solidgas) non-catalytic reaction. In addition to describing the setup and the theory behind the involved phenomena, this paper lists the main pedagogical objectives, and exemplifies the experimental procedures and mathematical treatments involved in the student work. Considering the successful results reported in the literature in what concerns the student's engagement and improvements in the learning process while using technological pedagogic support, a video on the procedure of this lab experiment has been produced and made available to students. A two-part inquiry was made at the end of the class term, assessing the students feedback on general aspects of the work (part 1) and on the demonstrative video (part 2). It was concluded that most students consider this work highly relevant for the better understanding of the involved concepts. Also, all the students who watched the video (87%) considered this kind of pedagogical support quite relevant, with 67% of these students voting 5 in a scale of 1 (non-relevant) to 5 (very relevant). (c) 2016 Institution of Chemical Engineers